2016
DOI: 10.21829/myb.2007.1321225
|View full text |Cite
|
Sign up to set email alerts
|

Fiber morphology in fast growth Gmelina arborea plantations

Abstract: Gmelina arborea is planted in large areas of forest with the objective of producing solid wood using well known silvicultural techniques and taking advantage of the properties of the wood quality of fast-growing tree species managed in short rotation systems. The aim of this study was to analyze the morphology and dimension of fibers from the pith to the bark in trees from fast growth plantations in northern Costa Rica.The results indicate that fiber morphology is irregular in both diameter and shape; with 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
1
1
Order By: Relevance
“…The fibre length of G. arborea of 1.5 mm average observed in the present study corroborates the report of Moya, Tomazelo and Canessa (2007), therefore strengthening the reliability of our data. The result from the present study on the fibre length shows that the average fibre length (L) of A. boonei was 1.70 mm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fibre length of G. arborea of 1.5 mm average observed in the present study corroborates the report of Moya, Tomazelo and Canessa (2007), therefore strengthening the reliability of our data. The result from the present study on the fibre length shows that the average fibre length (L) of A. boonei was 1.70 mm.…”
Section: Discussionsupporting
confidence: 92%
“…This observation indicates that papers produced from wood fibres of A. boonei is likely to have high tear resistance than those from the other wood samples studied. The fibre diameter of G. arborea observed in this study was higher than that reported by Moya et al (2007) and Ogunkunle (2010). Okereke (1962) reported that fibre with large diameter and broad lumen diameter ensures better collapsibility and therefore provides enough bonding surface during paper production.…”
Section: Discussioncontrasting
confidence: 80%
“…The species Antocleista grandiflora Gilg is native to the African continent, being found mainly in the countries of South Africa, South Sudan, Cameroon, and Comoros (KEW SCIENCE, 2021). Belonging to the Gentianaceae family, this plant species shows excellent growth in humid tropical biome regions, and its height can vary between 5 and 25 meters (NOTTEN, 2014;KEW SCIENCE, 2021;ROTICH et al, 2022). According to Mudau et al (2022), the roots and stems are extracted in fresh or dried states.…”
Section: Introductionmentioning
confidence: 99%